STRENGTHENING ENTREPRENEURIAL CAPACITY THROUGH STRUCTURED BUSINESS IDEATION AND INCUBATION: A COMMUNITY ENGAGEMENT MODEL - Gautama Sastra Waskita; Linggar Aura Damayanti; Sawal Sartono (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Tulungagung, 2026)
Universities are increasingly expected to foster student entrepreneurship, yet many campus-based incubation programs operate under highly compressed timelines, overstating financial milestones without evaluating operational failure modes or seasonal market biases. This community engagement program aimed to strengthen students’ entrepreneurial capacity through a structured business ideation and incubation model implemented within the Faculty of Economics, Universitas Tulungagung, while tracking quantitative competency improvements and operational variance across cohorts. Engaging 40 undergraduate students over a synchronized 8-week timeline, the intervention utilized a participatory community development approach integrating needs assessment, business ideation workshops, Business Model Canvas development, digital marketing training, a 4-week active incubation phase, and a final pitching evaluation. Data credibility was secured through the triangulation of field observations, documentation, semi-structured interviews with both high-performing and struggling cohorts, and paired pre- and post-test assessments. The results revealed significant quantitative competency gains, particularly in digital marketing (+29.30 points), alongside the operational deployment of student ventures like Racha Privat, Sakha Sweet, Dapur Santri, and Fresh Bite. While Racha Privat achieved a substantial revenue surge by the eighth week, this milestone was partially accelerated by seasonal market demands linked to academic examination periods. Conversely, product-based cohorts faced strategic friction, proving that high digital engagement does not automatically secure immediate transactional conversion. This study impacts future university-based entrepreneurial ecosystems by proving that sustainable student venture creation requires structured experiential models integrated with longitudinal post-incubation support and tailored financing.